2011
DOI: 10.1111/j.1365-2141.2011.08955.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of early T‐cell precursor acute lymphoblastic leukaemia: results of the Tokyo Children’s Cancer Study Group Study L99‐15

Abstract: Summary Early T‐cell precursor acute lymphoblastic leukaemia (ETP‐ALL) is a recently identified subtype of T‐ALL with distinctive gene expression and cell marker profiles, poor response to chemotherapy and a very high risk of relapse. We determined the reliability of restricted panel of cell markers to identify EPT‐ALL using a previously classified cohort. Then, we applied the cell marker profile that best discriminated ETP‐ALL to a cohort of 91 patients with T‐ALL enrolled in the Tokyo Children’s Cancer Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
141
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(157 citation statements)
references
References 19 publications
11
141
1
4
Order By: Relevance
“…67 Many studies reported poor outcome of ETP ALL, 67,68 but this is mitigated by contemporary risk-adapted therapy. 69,70 ETP ALL is genetically heterogeneous, with mutation of multiple cellular pathways including (1) hematopoietic and lymphoid development (RUNX1, IKZF1, ETV6, GATA3, and EP300); (2) Ras, cytokine receptor, and kinase signaling (NRAS, IL7R, KRAS, JAK1, JAK3, NF1, PTPN11, and SH2B3); and (3) loss-of-function mutations targeting epigenetic regulators.…”
Section: 66mentioning
confidence: 99%
“…67 Many studies reported poor outcome of ETP ALL, 67,68 but this is mitigated by contemporary risk-adapted therapy. 69,70 ETP ALL is genetically heterogeneous, with mutation of multiple cellular pathways including (1) hematopoietic and lymphoid development (RUNX1, IKZF1, ETV6, GATA3, and EP300); (2) Ras, cytokine receptor, and kinase signaling (NRAS, IL7R, KRAS, JAK1, JAK3, NF1, PTPN11, and SH2B3); and (3) loss-of-function mutations targeting epigenetic regulators.…”
Section: 66mentioning
confidence: 99%
“…5,6 This immature cluster shows a high level of enrichment of transcripts that are associated with early thymic precursor (ETP)-ALL, 22 a subgroup of T-ALL that exhibit a stem cell/immature myeloid-like immunophenotype, resistance to treatment and poor outcome. 15,[23][24][25][26] Genomic analysis of ETP-ALL has revealed high rates of mutations in factors involved in cytokine receptor and RAS signaling, hematopoiesis and epigenetic modification, 15 but the precise molecular basis of these patients' adverse prognosis remains unclear.…”
Section: An Early Thymic Precursor Phenotype Predicts Outcome Exclusimentioning
confidence: 99%
“…25,26,39,40 It remains to be seen whether similar strategies will improve the outcome of HOXA Pos adult ETP-ALL patients. The introduction of more intensive pediatric-based regimens has been central to recent improvements in the outcome of hitherto resistant adult ALL.…”
Section: A B C Dmentioning
confidence: 99%
“…The ETP immunophenotype is described as lack of CD1a and CD8, CD5-/dim þ , and expression of one or more myeloid or stem cell-related antigens. 18,19 Both studies focused on pediatric patients and did not further specify whether TdTnegative T-ALL/LBL cases fall into the ETP type of T-ALL/LBL.…”
mentioning
confidence: 99%